Burnout in oncologists and associated factors: A systematic literature review and meta‐analysis - Yates, Matthew; Samuel, Victoria (European journal of cancer care, 2019)
Background Oncologists may be particularly at risk of burnout. This systematic literature review and meta‐analysis explores the prevalence of burnout and associated factors in oncologists. Methods The authors assessed 26 studies that utilised the Maslach Burnout Inventory (MBI) tool to measure burnout. Pooled prevalence rates were calculated via meta‐analysis (MetaXL) using random effects models. Results Approximately 5,768 oncologists provided burnout data. A significant number experience burnout as highlighted by the pooled prevalence rates for MBI subscales of: emotional exhaustion at 32%; depersonalisation at 24%; and low personal accomplishment at 37%. Eighteen of the studies reported factors found to be significantly associated with high levels of burnout in oncology physicians. These were grouped into demographic differences, individual factors and work factors. Conclusion Burnout was found to affect a significant proportion of oncologists. Burnout was associated with being single, being younger in age, reduced psychological well‐being, difficulties outside of work, workplace demands and workplace stress. Burnout has considerable implications for oncology physicians and patient safety. Further insight into individual factors, and factors associated with lower burnout would be beneficial.